Renting vs. Owning: Public Stereotypes of Housing Consumption Decision From the Perspective of Confucian Culture: Evidence From Event-Related Potentials - Liu, Xiaojun; Yu, Mingqi; Cheng, Baoquan; Fu, Hanliang; Guo, Xiaotong (Frontiers in Psychology, 2022)
The ideas of face consciousness, group conformity, extended family concept and crisis consciousness in Confucian culture have a subtle and far-reaching impact on housing consumption decision among the Chinese public, forming a housing consumption model of “preferring to own a house rather than rent one”. The poor interaction between the housing rental market and the sales market caused by the shortage of rental demand and irrational purchasing behaviors has led to soaring house prices and imbalance between supply and demand that prevail in major cities in China. To gain a deeper understanding of public cognitive attitude towards decisions on owning and renting a house, this study divided the subjects into high and low impact groups based on the overall Confucian culture and four subdimensions. It attempts to take a cognitive neuroscience approach for assessing public stereotypes of housing consumption decision with different types based on the analysis of event-related potentials (ERPs). The results are as follows. First, overall, there is an obvious implicit stereotype of renting a house and explicit stereotype of owning a house among the public. Second, ERPs data show that descriptions of renting a house with positive adjectives could evoke more significant N400 responses. In other words, in the heuristic system, the public perceive that renting a house is restrictive, stressful, unhappy, and crisis. Data from subjective reports show that, after processing information in the analytic system, the public tend to think that owning a house is self-contained, restful, warm, comfortable. Third, a more negative stereotype of renting a house exists in the HIC Group than in the LIC Group, and is more inclined to own a home. Fourth, under the Confucian culture sub-dimension, there are differences in housing consumption stereotypes between high and low groups in terms of extended family concept, group conformity and crisis consciousness. Fifth, the moderating effect analysis found that perceived usefulness, trust in the rental market, and policy perception can be important factors in guiding public housing consumption stereotypes.